(untitled) (Research, Society and Development, 2022)
Purpose: to analyze the Speech-Language Pathology production on the topic, as well as the definition of descriptor (first), defense institution (geographical location), life cycle and total sample included in Brazilian dissertations and theses defended between 2017-2021. Method: this is a bibliometric study that included data collected on the Brazilian Digital Library of Theses and Dissertations, on March 28, 2022 using the term fonoaudiologia [speech-language pathology] and within a mentioned period and variables. Data were analyzed descriptively and inferentially (p≤5%). Results: among the 543 entries retrieved, 399 (73.5%) were dissertations, most of which were defended in 2018 (177; 32.6%), in the Southeast region (321; 59.1%), in the State of São Paulo (293; 54%) and at the Universidade de São Paulo (135; 24.9%). As for the topic, the most investigated subjects were Language (165; 36.1%) and Audiology (145; 31.7%), referring to childhood (202; 40.2%), with a median sample of 36 participants. In addition, Speech-Language Pathology, Hearing and Voice were the most used descriptors in the studies. No significant difference was found regarding the topic and increase in literature review works when comparing the defenses that occurred before (476; 87.7%) and during the pandemic (67; 12.3%). Conclusion: Language and Hearing are the most investigated topics, being defended mainly in the Southeast region (especially São Paulo), due to the high number of Programs, since the beginning of the profession. Childhood (prioritized in the early days of Speech-Language Pathology) continues to be the most studied period of life. Although wrongly, the term Speech-Language Pathology was found more frequently as the first descriptor. Although the pandemic seems to have impacted the number of defenses, there was no impact on the profile regarding the type of work and topic.